Katalog der in den Sammlungen des ehemaligen Deutschen Entomologischen Institutes aufbewahrten Typen - XIII (Diptera: Cyclorrhapha: Division Aschiza). - Rohlfien, Klaus; Ewald, Birgit (Contributions to Entomology = Beiträge zur Entomologie, 1975)
This is the third contribution to the catalogue of types of the collection of Diptera of the Department of Taxonomy of Insects (former Deutsches Entomologisches Institut) of the Institute of Plant Protection. It contains all the types as far as the subspecies of the division Aschiza (suborder Cyclorrhapha). The species are listed in alphabetical order within the families, which are named and arranged according to the "Catalog of the Diptera of America North of Mexico" (1965). It is attempted to explain contradictions between the original quotations and the statements in the collection, suggestions for the establishment of types are made for the use of the specialists, and the state of preservation is noted.